Female tilapia, Oreochromis sp. mobilised energy differently for growth and reproduction according to living environment - Ros Suhaida Razali; Sharifah Rahmah; Yu Ling Shirly‑Lim; Mazlan Abd Ghafar; Suhairi Mazelan; Mohamad Jalilah; Leong‑Seng Lim; Yu Mei Chang; Li Qun Liang; Young‑Mao Chen; Hon Jung Liew (National Library of Medicine, 2024)
This study was conducted to investigate the energy mobilisation preference and ionoregulation pattern of female tilapia, Oreochromis sp. living in diferent environments. Three diferent treatments of tilapia as physiology compromising model were compared; tilapia cultured in recirculating aquaculture system (RAS as Treatment I—RAS), tilapia cultured in open water cage (Treatment II—Cage) and tilapia transferred from cage and cultured in RAS (Treatment III—Compensation). Results revealed that tilapia from Treatment I and III mobilised lipid to support gonadogenesis, whilst Treatment II tilapia mobilised glycogen as primary energy for daily exercise activity and reserved protein for growth. The gills and kidney Na+ /K+ ATPase (NKA) activities remained relatively stable to maintain homeostasis with a stable Na+ and K+ levels. As a remark, this study revealed that tilapia strategized their energy mobilisation preference in accessing glycogen as an easy energy to support exercise metabolism and protein somatogenesis in cage culture condition, while tilapia cultured in RAS mobilised lipid for gonadagenesis purposes.